Buried treasure – the teaching potential of Kodachrome slides brought into the digital age. (27th June 2021) - Zufall, Alina Gertrud; Mark, Erica Jaclyn; Pollack, Karlyn; Russell, Mark
Abstract: Clinical images on Kodachrome slides have been used for decades in dermatologic education. While the technology to view these images is becoming obsolete, many training programs possess high‐quality slides that have educational benefit. The University of Virginia Department of Dermatology possesses a collection of such slides that are currently being digitized and integrated into an educational software program. We present this article as a means of providing a uniform protocol for institutions with large Kodachrome collections to do the same. Our work has proven beneficial for both medical students interested in dermatology, allowing them to gain exposure to a variety of conditions that are not well emphasized in the general curriculum, as well as for dermatology residents, who use the program as a means to hone their diagnostic skills. Not only is there educational benefit to be derived from digitizing these slides but time is of the essence, as these slides can easily become damaged or degraded, and the technology needed to scan them is quickly becoming less available.